Preferencje konsumenckie w zakresie mleka i jego przetworów - Górska-Warsewicz, Hanna; Kowrygo, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
The objective of the study was to evaluate the consumer preferences regarding milk and its products. The research was conducted in February 1996 with the use of the questionnaire method. The assortment of dairy products was assessed as satisfactory by the majority of respondents. The most important factor influencing the purchase of milk, ice-cream and other cheeses was price, while in the case of milk beverages, cottage cheese and ripening cheese - the size of packaging. The most seldom named factors were advertisement and planned menu.